Pengaruh Pengungkapan Sukarela terhadap Kinerja Keuangan dengan Cost of Capital sebagai Variabel Intervening - Nana Nofianti; Abdul Fatah; Novita Tirtasari (Journal of Applied Accounting and Taxation, 2018)
This study aimed to analyze the influence of voluntary discloure on financial performance with cost of capital as an intervening variable. Voluntary disclosure is measured by an index, financial performance in proksikan with Return on Asset and cost of capital is proxied by the CAPM. The sample in this study are as many as 55 companies, and samples used in this study is a manufacturing company listed on the Indonesia Stock exchange. The statistical method used is regression analysis with path analysis. Based on the test results showed that the index Voluntary Disclosure affect corporate financial performance. Voluntary Disclosure Index was observed to have an influence on cost of capital. Cost of capital have an influence on the financial performance and cost of capital mediate the association of voluntary disclosure and financial performance.